STATUS OF WOMEN IN PRE MODERN KERALA, WITH SPECIAL REFERENCE TO TRAVANCORE - Keerthana Santhosh
Kerala Model Development, Gods own country, the most literate state and so forth are nothing but common adjectives to Kerala. Behind the glorious achievements, one can find the fair hand of the fair sex. This is not an exaggeration. Being the most literate and most progressive state, Kerala owes much to women. Travancore was the southernmost native state of India and was merged with Cochin and Malabar to form the present state of Kerala in 1956. The state is hailed everywhere for its Human Development Indices, progress, women empowerment, transgender policy etc. Virtually, there is no gender disparity in Kerala. Women occupy the same status and position as that of their counterparts. But it was not the situation. The present study tries to trace the condition of women in pre modern Kerala, particularly in Travancore.